CONCEPTION OF LEGAL PROTECTION IN ISLAMIC LAW - Idrus, Achmad Musyahid (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2019)
Legal protection is a human right which is a basic need for every human being, both human beings as legal subjects and human beings as legal objects. As legal subjects, humans have civil rights that must be implemented in accordance with applicable legal provisions. Likewise with humans as legal objects, their rights must still be protected even though they have been convicted by law. Sometimes legal protection for humans cannot be realized because the source of the applicable law does not provide legal instruments and even the protection of the law does not materialize because of the lack of understanding of the source of the law which applies in society.Islamic law as one source of law and adopted in countries like Indonesia offers the conception of legal protection in accordance with the dignity and human rights, because of the flexibility of Islamic law, so that Islamic law can be understood and adjusted to the social development of the society. Islamic law that emphasizes public benefit guarantees the legal protection needed by the community, but the values of flexibility must still be explored from the main sources of the Qur'an and the hadith of the prophet.